Biological effects of decabromodiphenyl ether (BDE209) and Pb on earthworm (Eisenia fetida) in a soil system. (December 2015) - Li, Jing; Zhang, Wei; Chen, Lin; Liang, Jun; Lin, Kuangfei
Abstract: BDE209 and Pb are ubiquitous contaminants at e-waste recycling sites (EWRSs). This study aimed to determine acute and sub-acute toxicity to earthworm Eisenia fetida induced by BDE209 and Pb in natural soil. Results demonstrated that the inhibition of Pb on growth and reproduction of earthworms followed a dose-dependent pattern. Earthworms exposed to 100 mg kg −1 of BDE209 displayed avoidance responses, while the soil indicated a more obvious decline of habitat function with the increase of Pb level. Comet assay suggested that increasing concentrations of Pb exposure resulted in a gradual increase in the tail length and olive tail moment, which meant that the degree of DNA damage was promoted. BDE209 addition could reduce the damage; therefore the joint effects of both chemicals showed antagonistic. These results revealed that joint exposure (BDE209-Pb) could elicit pronounced biochemical and physiological responses in earthworms, and the DNA damage might be potential molecular biomarker of the two pollutants. Highlights: 48 h and 14 d LC50 values of BDE209 were lower than that of Pb, suggesting Pb was more toxic to earthworms. Inhibition of Pb on the growth and reproduction of earthworms followed certain dose–response relationships. Joint effects of BDE209 and Pb on earthworms might be antagonistic in comet assay. Abstract : This study demonstrated the biological effects of BDE209-Pb joint exposure on earthworm Eisenia fetida in a soil system for the first time.